Pre-existing cardiovascular disease and hyperlipidemia and mortality in peritoneal dialysis patients - Cao, Panpan; Zhan, Xiaojiang; Wen, Yueqiang; Feng, Xiaoran; Peng, Fenfen; Wu, Xianfeng; Wang, Xiaoyang (Frontiers in Endocrinology, 2025)
ObjectivesThis study aimed to evaluate the impact of pre-existing cardiovascular disease (CVD) and dyslipidemia on mortality in patients undergoing continuous ambulatory peritoneal dialysis (CAPD).MethodsThis study was conducted as a multicenter retrospective cohort investigation. Eligible patients newly diagnosed with CAPD between January 1, 2005 and December 31, 2018 were enrolled in this study. Missing data were handled using the missForest imputation method. The primary outcome was all-cause mortality. All patients were followed until the cessation of peritoneal dialysis, death, completion of the 8-year follow-up period, or June 30, 2019, whichever occurred first.ResultsAmong the 2939 patients, 2132 (72.5%) had no pre-existing CVD or hyperlipidemia, 397 (13.5%) had hyperlipidemia alone, 274 (9.3%) had pre-existing CVD alone, and 136 (4.6%) had pre-existing CVD and hyperlipidemia. The median observational period was 33.6 (IQR 15.6–60.8) months. The number of deaths from all causes were 72 (36.8%), 67 (16.9%), 96 (35.0%), and 306 (14.4%) in the pre-existing CVD plus hyperlipidemia, hyperlipidemia alone, pre-existing CVD alone, and control groups, respectively. After adjusting for confounding factors, patients with pre-existing CVD alone, hyperlipidemia alone, and patients with both conditions had 1.41 (95% CI 1.03 to 1.94), 0.98 (95% CI 0.75 to 1.28) and 1.47 (95% CI 1.16-1.88)-fold greater risk of all-cause mortality, respectively, than patients without pre-existing CVD and hyperlipidemia. Notably, among patients with pre-existing CVD, hyperlipidemic patients had a higher risk of mortality than patients without hyperlipidemia (hazard ratio 0.89, 95% CI 0.61 to 1.31). Among patients without pre-existing CVD, hyperlipidemic patients had a higher risk of mortality than patients without hyperlipidemia (HR 1.10, 95% CI 0.83 to 1.48). There was no interaction effect between the coexistence of pre-existing CVD and hyperlipidemia, pre-existing CVD alone, and hyperlipidemia alone on all-cause mortality (β = 0.221, P = 0.976).ConclusionIn patients undergoing CAPD, the coexistence of pre-existing cardiovascular disease and hyperlipidemia is associated with a significantly higher risk of all-cause mortality. This finding suggests that the comorbidity may contribute to worse long-term outcomes and highlights the importance of dyslipidemia management in clinical practice.